Directed Manipulation With Respect To Focal Rings - Edge, Darren; Ding, Xianghua (BCS-HCI 2009 British HCI Group Annual Conference on People and Computers, 2009)
In this paper we describe the notion of a focal ring interface: an interface comprising a centrally-located graphical ring that provides a visual focus for interaction with respect to itself and its associated representation (such as a map, media collection, or information hierarchy). Our focal rings provide an opportunity to assign independent effects to the two dimensions of a display surface, creating implicit gestural modes (e.g. navigation versus scaling) that can be dynamically switched between in the context of a single continuous stroke. A focal ring can define the origin of a Polar or Cartesian frame of reference, interpreting touch gestures directed either through and around, or horizontal and vertical to itself. We illustrate the potential for such directed manipulation with respect to focal rings through the design and evaluation of ring-centric interfaces based on a variety of physical metaphors.